2008
DOI: 10.1063/1.3023155
|View full text |Cite
|
Sign up to set email alerts
|

Exponential frequency spectrum and Lorentzian pulses in magnetized plasmas

Abstract: Two different experiments involving pressure gradients across the confinement magnetic field in a large plasma column are found to exhibit a broadband turbulence that displays an exponential frequency spectrum for frequencies below the ion cyclotron frequency. The exponential feature has been traced to the presence of solitary pulses having a Lorentzian temporal signature. These pulses arise from nonlinear interactions of drift-Alfvén waves driven by the pressure gradients. In both experiments the width of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
79
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(85 citation statements)
references
References 39 publications
6
79
0
Order By: Relevance
“…Somewhat similar localized bloblike temperature filaments have been created in the linear plasma device LAPD. 217 Such external control of blobs has not been possible in fusion devices, mainly due to the large energy and particle flux already existing in normal conditions in these devices.…”
Section: E Location and Structurementioning
confidence: 99%
“…Somewhat similar localized bloblike temperature filaments have been created in the linear plasma device LAPD. 217 Such external control of blobs has not been possible in fusion devices, mainly due to the large energy and particle flux already existing in normal conditions in these devices.…”
Section: E Location and Structurementioning
confidence: 99%
“…The LAPD edge fluctuations have the highest level of complexity of the three measured data sets and occupy a middle region in terms of the permutation entropy. Previous work has shown that the LAPD drift-wave turbulence may be dominated by nonlinear interactions of relatively small numbers of modes, and thus tend to exhibit more chaotic, complex behavior [16]; thus, its coordinates occupy a position closest to known chaotic maps. Finally, the SSX fluctuations exhibit a level of complexity in between the other two plasmas.…”
Section: Introductionmentioning
confidence: 99%
“…The solar wind is highly variable but there are two broad types: fast wind (V > 600 km/s) which is emitted from open coronal field lines and is typically low density (<5 protons/cm 3 ), has few large scale structures and has high amplitude but less developed turbulence, and slow wind, (V < 500 km/s) which is typically found in the ecliptic plane and originates from more complex coronal magnetic topology and is denser and more structured than the fast wind with more evolved but lower amplitude turbulence [26,27]. Here we use multiday long intervals of a fast wind stream (January [14][15][16][17][18][19][20][21]2008) and a slow wind stream (January [24][25][26][27][28][29]2010) with large scale magnetic fluctuations on the order of 10 nT.…”
Section: Introductionmentioning
confidence: 99%
“…However, the log-log display format compresses a large dynamic range of the data and thus it can obscure important underlying features of the fluctuations, as has been recently found in experiments performed in a linear device. 24 The studies in the large plasma device (LAPD) by Pace et al 24 considered two different situations in which crossfield pressure gradients were created in a magnetized plasma column. One was a pure temperature gradient consisting of a hot electron channel surrounded by a cold plasma.…”
Section: Introductionmentioning
confidence: 99%